Effect of posttransportation grazing on the physiological condition and meat quality traits of Black Bengal goats. (16th December 2018) - Salahuddin, Md.; Azad, Md. Abul Kalam; Das, Shonkor Kumar; Hossain, Mohammad Mujaffar; Hasan, Md. Nazmul; Hiramatsu, Kohzy
Abstract: This study was designed to reveal the role of posttransportation grazing on the physiological condition and meat quality traits of Black Bengal goats. Twenty‐four castrated male Black Bengal goats were divided into a control (untransported) group and three treated groups: Walking and Transportation with Human Interference group (WTHI) (30 min walking before 6 hr transport and then 30 min walking with human interference), posttransportation grazing for 48 hr (PTG1), and posttransportation grazing for 72 hr (PTG2). The WTHI and PTG1 groups had a significant reduction in their blood concentrations of tri‐iodothyronine (T3 ) and thyroxine (T4 ), and a significantly higher neutrophil and lymphocyte (N:L) ratio compared with those of the control group. Blood concentrations of T3 and T4 and the N:L ratio of PTG2 returned to the control level after 72 hr of grazing. The final pH and water‐holding capacity values of meat were significantly higher in the WTHI group than in the control group, but those in the PTG2 group returned to the control level after 72 hr of grazing. These results demonstrate that posttransportation grazing for 72 hr is effective for recovering from damage induced by transportation stress.